Socio-demographic and socio-economic profile of tribal communities in East Godavari district, Andhra Pradesh - Gutta, Sravana Kumar; Kothapalle, Sowmyasudha; Goru, Krishnababu; Kadali, Satyanarayana (International Journal Of Community Medicine And Public Health, 2019)
Background: Scheduled tribes live in unique physical, socio-economic and cultural environment isolated from general population. The tribal population is at a higher risk of under-nutrition and Malaria, because of the socio-cultural, socio-economic and environmental factors influencing health seeking behaviour. We made an attempt to study the socio demographic economic variables in the tribal communities of East Godavari district. Methods: A pre-tested questionnaire containing information on household socio-economic and demographic particulars like type of family, religion, caste, age, gender, income, literacy and occupation, was administered by paying house to house visits. All the data were entered into excel sheets and analyzed by using SPSS software 17. Results: 59.25% were literates. 56.25% belongs to monthly income less than 773 rupees i.e. class-5, 74.29% are living in nuclear families. 48.55% belongs to Konda Reddy community. 56.69% have access to mineral water supply. 89.78 – 98.94% does not have toilets in their houses. 43.39% of the respondents have cattle sheds near to their houses. Conclusions: More than half of the tribal’s needs to improve their socio-demographic and socio-economic conditions. Still it needs construction of community toilets or individual toilets in tribal areas.